Willingness to receive COVID-19 vaccination among adults with chronic diseases in the Kingdom of Saudi Arabia - Mohammed K. Al-Hanawi; Kabir Ahmad; Rezwanul Haque; Syed A. Keramat (Elsevier, 2021)
Background: People with chronic conditions such as cancer, kidney disease, lung disease, diabetes, dementia, obesity, and heart conditions are at elevated risk of developing severe complications, and are thus at greater risk of death due to COVID-19. The COVID-19 vaccine is an effective measure to manage the pandemic as it prevents severe illness and death. Nevertheless, many people are hesitant to receive the COVID-19 vaccine due to fear of its side effects. The aim of this study was to identify the risk and protective factors of accepting COVID-19 vaccination among Saudi Arabian people with chronic diseases. Methods: This study extracted data from an online cross-sectional self-reported questionnaire conducted on the acceptability of a COVID-19 vaccine in Saudi Arabia in December 2020. The study included a sample of 521 adults who self-reported that they had chronic diseases. Multivariable regression analyses were employed to identify the factors associated with accepting COVID-19 vaccination in Saudi Arabia. The estimates were adjusted for confounding variables, including socio-demographic factors. Results: Among the sampled participants of Saudi adults with chronic diseases, approximately 52% indicated that they were willing to accept the COVID-19 vaccine. Participants had higher willingness to accept the vaccine if they received the seasonal influenza vaccination in the past [odds ratio (OR): 2.179; 95% confidence interval (CI): 1.222-3.888], reported high or very high levels of concern about contracting COVID-19 (OR: 2.426; 95% CI: 1.209-4.867), or believed in mandatory COVID-19 vaccination (OR: 84.848; 95% CI: 37.651-191.207). Participants had lower willingness to be vaccinated if they had a history of vaccine refusal (OR: 0.211; 95% CI: 0.088-0.504). Among the socio-demographic factors, being male (OR: 2.153; 95% CI: 1.007-4.603), having a postgraduate degree (OR: 2.408; 95% CI: 0.985-5.886), and being unemployed (OR: 2.780; 95% CI: 0.876-8.827) were associated with an increased willingness of receiving the COVID-19 vaccine. Conclusions: The findings of this study demonstrate that willingness to receive COVID-19 vaccination among Saudi Arabian adults with chronic conditions is low. Therefore, further policy measures are required to manage COVID-19-related infections and the death toll.